Probing whole‐stream metabolism: influence of spatial heterogeneity on rate estimates. (31st January 2017) - Siders, Adam C.; Larson, Danelle M.; Rüegg, Janine; Dodds, Walter K.
Summary: Whole‐stream metabolism has been estimated by measuring in‐stream oxygen (O2 ) concentrations since the method was introduced over 50 years ago. However, the influence of measurement location and estimation method on metabolism rates is understudied. We examined how the placement of O2 probes (i.e. depth, separation from the thalweg), differences in methodology (1‐station, 2‐station, area‐weighted) and reach lengths influenced estimated rates of whole‐stream metabolism in a tallgrass prairie watershed. Metabolism estimates made in the thalweg differed from estimates made in backwaters due to disconnection in flow, and estimates made in deep pools differed from surface estimates due to thermal stratification (temporary flow disconnection). The 1‐station respiration estimates differed from short 2‐station reach‐scale estimates ( c . 20 m) but were more similar to larger 2‐station reach‐scale estimates ( c . 100 m). In contrast, the 1‐station gross primary production was most similar to the short 2‐station reaches occurring immediately upstream and became less similar at longer 2‐station reach lengths. The different estimation methodologies (1‐station, 2‐station, area‐weighted) accounting for the longest reach scale did not result in different metabolism rates. The temporary phenomena of thermal stratification of stream pools during a warm day, which disconnected pool bottoms from the surface waters, likely affected not only the pool estimates but also estimates made in the downstream thalweg (i.e. an O2 deficit accrued from respiration during the day in the bottom of the pool abruptly moved downstream during mixing). Oxygen probe placement mattered and affected rate estimates according to habitat type and reach length (i.e. scale) due to the influence of small‐scale heterogeneity on community respiration. Selection of reach length can be critical for studies depending on whether local heterogeneity is of interest or should be averaged. We conclude that the intuitive use of thalwegs and reaches that are at least 10 times the stream width are likely appropriate for whole‐stream metabolism estimates, although the exact reach length necessary and potential stream‐specific characteristics, such as stratified pools, need to be carefully considered in probe placement. We encourage other studies to report the placement characteristics of O2 probes in streams as well as consider the potential confounding factor of local habitat heterogeneity.